The demographics of patients presenting for sexual assault to US emergency departments. (January 2020) - Loder, Randall T.; Robinson, Tyler P.
Abstract: Background: Few studies address the demographics/epidemiology of patients presenting to emergency departments (ED) for evaluation of sexual assault across an entire nation. It was the purpose of this study to analyze the demographics of sexual assault using a national data base. Methods: This was a retrospective study of prospectively collected data from National Electronic Injury Surveillance System - All Injury Program for years 2005–2013. Patients presenting for sexual assault were analyzed. Descriptive and logistic regression statistical analyses were performed with SUDAAN 11.0.01™ software. A p < 0.05 was considered statistically significant. Results: Sexual assault accounted for an estimated 657, 719 ED visits (0.24% of all injuries, and 3.4% of injuries due to violence). When an assault victim presented to the ED, a sexual assault was most likely when the patient was 0–14 years old (OR = 19.48 [12.02, 31.57]), White (OR = 2.12 [1.30, 3.47]), the perpetrator being a stranger (OR = 10.51 [8.21, 13.46]), and occurring at home (OR = 10.05 [6.61, 15.27]). The average annual incidence of ED visits for sexual assault per 10, 000 US population was 2.39; 0.47 for males and 4.92 for females. The average was 19.6 years; 90.3% were female. Assaults occurred in the home in 45.6%, and were more common in the summer. The perpetrator was unknown in 37.5%, a friend/acquaintance in 24.8%, other relative in 9.4%, multiple perpetrators in 9.3%, spouse/partner in 6.8%, with the remaining 12.7% from other groups. Racial composition was White in 60.9%, Black in 25.9%, Amerindian in 12.5%, and Asian in 0.5%. The perpetrator was a close relative nearly twice as frequently for male victims compared to female victims. Hospital admission overall was 2.7%: 7.1% when the assault occurred on the street, 1.8% when at school or sporting locations, 4.9% for males and 1.5% for females. Nearly all (98.2%) extremity injuries occurred in females. Conclusions: Sexual assaults account for 4.4% of ED visits for violence. There was a decrease in the number of sexual assaults occurring on the street and at school/sporting locations over time while the number of assaults by strangers increased. For males, 54.1% occurred in those <10 years of age. The differences between patients by demographic and event characteristics is important information for health care providers. Highlights: Sexual assault ED visits comprise 4.4% of those due to violence; 45.6% occur at home. The average age was 14.0 years for male and 19.1 years for females. The perpetrator was a close relative nearly twice as frequently for male victims.